2017
DOI: 10.3390/molecules22091542
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Alleviates Alkaline Stress in Malus hupehensis Rehd. by Regulating the Biosynthesis of Polyamines

Abstract: Since melatonin was identified in plants decades ago, much attention has been devoted to discovering its role in plant science. There is still a great deal to learn about the functional importance of melatonin, as well as its functional mode. In this paper, we examine the role of melatonin treatment in the response of Malus hupehensis Rehd. to alkaline conditions. Stressed seedlings showed chlorosis and suppressed growth. However, this phenotype was ameliorated when 5 µM melatonin was added to the irrigation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 67 publications
(77 reference statements)
3
50
0
Order By: Relevance
“…The most obvious phenotype is the yellowing phenomenon of leaves in response to alkaline conditions, which showed a decrease of chlorophyll content [5,28]. In this study, compared with control, the contents of chl a, chl b, and chl t significantly decreased under alkali stress, as seen in Figure 5A-C.…”
Section: Pn Chlorophyll Content and Fv/fmsupporting
confidence: 50%
See 1 more Smart Citation
“…The most obvious phenotype is the yellowing phenomenon of leaves in response to alkaline conditions, which showed a decrease of chlorophyll content [5,28]. In this study, compared with control, the contents of chl a, chl b, and chl t significantly decreased under alkali stress, as seen in Figure 5A-C.…”
Section: Pn Chlorophyll Content and Fv/fmsupporting
confidence: 50%
“…The effects of alkali stress on plant growth mainly manifested in the damage of partial root function, decreases of water content and root activity, destruction of the photosynthetic system, and a decrease of photosynthetic pigment levels [3]. Previous studies have shown that alkali stress can significantly inhibit the growth of apple seedlings, damage plasma membrane, and cause a series of reductions of physiological functions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, greater SOD activity has been reported during chilling stress [42], waterlogging [44], alkaline stress [46], heavy metal stress [38], and drought stress [26]. Campos et al [25] reported that SOD activity was lower following the rehydration of Coffea arabica L. plants that had initially been exposed to drought stress, whereas Hodžić et al [40] described changes in SOD activity following the addition of melatonin under Cd and Zn stress in Melissa officinalis L. and Valeriana officinalis L. Interestingly, lower SOD activity was observed in Valeriana officinalis L. supplemented with both Zn and melatonin, whereas it increased when Zn was replaced with Cd.…”
Section: Superoxide Dismutase (Sod)mentioning
confidence: 72%
“…POD, CAT [44] Pisum sativum L. Oxidative stress SOD [45] Malus hupehensis Rehd. Alkaline stress SOD, POD, CAT [46] Citrullus lanatus Vanadium stress SOD, CAT [47] Arabidopsis thaliana High light stress APX [48] Trigonella foenum graecum L. Lead and acid rain stress SOD, CAT [49] Solanum lycopersicon cv. Salinity and heat stress CAT, APX, GR, GST, GPX MDHAR SOD [50] Cynodon dactylon L. Salinity, drought and cold stress POD, SOD, CAT, GSH [51] Table 2.…”
Section: Crop Plantmentioning
confidence: 99%
“…17 There is broad evidence that melatonin protects plants from oxidative damage and harmful environmental conditions. 18,19 In addition to direct ROS scavenging, melatonin protects plant cells by chelating heavy metals and preventing the formation of free radical species. 20 The available knowledge about the effect of melatonin on the antioxidant metabolism of plants exposed to various types of abiotic stress is summarized in Table S-I of the Supplementary material to this paper.…”
Section: Introductionmentioning
confidence: 99%